2007
DOI: 10.3324/haematol.10701
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile hemochromatosis caused by a novel combination of hemojuvelin G320V/R176C mutations in a 5-year old girl

Abstract: LETTERS TO THE EDITORJuvenile hemochromatosis caused by a novel combination of hemojuvelin G320V/R176C mutations in a 5-year old girl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 10 publications
1
18
0
2
Order By: Relevance
“…The availability of the causative mutation is also useful for genetic counseling of family members. This information offers the possibility of early diagnosis in relatives and may help prevent severe complications, as in JH (36 ). …”
Section: Clinical Chemistrymentioning
confidence: 99%
“…The availability of the causative mutation is also useful for genetic counseling of family members. This information offers the possibility of early diagnosis in relatives and may help prevent severe complications, as in JH (36 ). …”
Section: Clinical Chemistrymentioning
confidence: 99%
“…Juvenile hemochromatosis (JH) is a rare autosomal recessive disorder of iron overload which affects young patients and usually leads to organ damage (cardiomyopathy, hypogonadotrophic hypogonadism, liver disease, and endocrine disturbances) before the age of 30 [1,2] . Here, a case with both clinical and molecular diagnosis of JH in which the adjuvant use of deferasirox therapy presented significant improvements in both biochemical and clinical disease control is reported.…”
mentioning
confidence: 99%
“…The girl displayed elevated iron indices without presenting clinical manifestations of juvenile hemochromatosis. 3 We simultaneously detected the p.R176C substitution at the homozygous state in a 17-year-old female of French Caucasian ancestry. At diagnosis, the teenager presented with a transferrin saturation of 97% and a serum ferritin concentration above 2,000 µg/L.…”
Section: Phenotypic and Functional Data Confirm Causality Of The Recementioning
confidence: 99%
“…destabilization of a short helix forms by the R176, S177 and F178 residues) 3 , it could be suggested that the p.R176C mutant is not efficiently cleaved. It would not, therefore, be able to induce the hepcidin gene transcription from the cell surface.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%